Epidemiology of Diabetes Mellitus among 193, 435 Cats Attending Primary‐Care Veterinary Practices in England. (29th June 2016) - O'Neill, D.G.; Gostelow, R.; Orme, C.; Church, D.B.; Niessen, S.J.M.; Verheyen, K.; Brodbelt, D.C.
Abstract : Background: Diabetes mellitus (DM) is a common endocrine disease of cats. The prevalence of DM in cats in England is not well‐defined. Hypothesis/Objectives: To estimate the prevalence and identify risk factors for DM in a large population of cats attending primary‐care practices. Animals: A cohort of 193, 563 cats in the VetCompass Programme attending 118 primary‐care practices in England. Methods: Cross‐sectional analysis of cohort clinical data. Data were extracted covering September 1st 2009 and August 31st 2014. Period prevalence of DM was calculated. Associations between risk factors and DM were assessed using logistic regression modelling. Results: Of 1, 128 DM cases were identified among 194, 563 cats (period prevalence 0.58%; 95% confidence interval [CI] 0.54–0.61). Multivariable modelling indicated that Tonkinese (OR 4.1; 95% CI 1.8–9.6; P = .001), Norwegian Forest (odds ratio [OR] 3.5; 95% CI 1.3–9.6; P = .001) and Burmese (OR 3.0; 95% CI 2.0–4.4; P < .001) cats had increased odds of DM compared with crossbred cats. DM odds increased as bodyweight categories increased above 4 kg ( P < .001), as cats aged beyond 6 years old ( P < .001) and in insured cats (OR 2.0; 95% CI 1.6–2.4; P < .001) but sex was not significantly associated with DM. Conclusions and Clinical Importance: Diabetes mellitus is an important component of the primary‐care practice caseload with 1‐in‐200 cats affected. An increased risk of DM in certain cat breeds supports a genetic predisposition. These results can guide future research and preventative healthcare.